2008
DOI: 10.1038/sj.bjp.0707639
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of polyacetylenes and polyenes isolated from roots of Echinacea pallida

Abstract: Background and purpose: The n-hexane extracts of the roots of three medicinally used Echinacea species exhibited cytotoxic activity on human cancer cell lines, with Echinacea pallida found to be the most cytotoxic. Acetylenes are present in E. pallida lipophilic extracts but essentially absent in extracts from the other two species. In the present study, the cytotoxic effects of five compounds, two polyacetylenes (namely, 8-hydroxy-pentadeca-(9E)-ene-11,13-diyn-2-one (1) and pentadeca-(9E)-ene-11,13-diyne-2,8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 33 publications
(50 reference statements)
7
45
0
2
Order By: Relevance
“…Apart from its anti-inflammatory activity, Bauer ketone 24 (compound 2) from E. pallida has also been reported to inhibit the growth of human cancer cell lines possibly by arresting the cell cycle in the G1 phase and promoting apoptotic cell death (Chicca et al, 2010). Bauer ketone 24 (compound 2) is evidently permeable above 10 × 10 −6 cms −1 across the Caco-2 monolayer, suggesting potential oral bioavailability (Chicca et al, 2008). Therefore, Bauer ketone 24 (compound 2) might be a promising candidate as an anti-inflammatory and anti-tumor agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its anti-inflammatory activity, Bauer ketone 24 (compound 2) from E. pallida has also been reported to inhibit the growth of human cancer cell lines possibly by arresting the cell cycle in the G1 phase and promoting apoptotic cell death (Chicca et al, 2010). Bauer ketone 24 (compound 2) is evidently permeable above 10 × 10 −6 cms −1 across the Caco-2 monolayer, suggesting potential oral bioavailability (Chicca et al, 2008). Therefore, Bauer ketone 24 (compound 2) might be a promising candidate as an anti-inflammatory and anti-tumor agent.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-inflammatory activity has been observed with a polysaccharide fraction and with polyunsaturated alkamides from E. angustifolia roots, and echinacoside, alkamides and polyenes/polyacetylenes from E. pallida (LaLone et al, 2007; LaLone et al, 2009; Tubaro et al, 1987). In addition, polyenes and polyacetylenes from E. pallida roots have also been reported to induce apoptosis of tumor cells (Chicca et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Reyes-Zurita et al found that maslinic acid induces apoptosis in HT29 colon cancer cells via the mitochondrial apoptotic pathway [69]. Furthermore, NPs with other structures, such as polyacetylenes and polyenes [72], chromane derivatives [73], grifolin [74], g-oryzanol [75], yuanhuacine [76], chartreusin [77] and statins [78], have been explored for the purpose of drug discovery for CRC ( Table 5). In addition, NPs derived from organisms in marine environments have recently been investigated.…”
Section: Other Nps For Anti-cancer Drug Discoverymentioning
confidence: 98%
“…Honokiol [65], magnolol [66], podophyllotoxin, silibinin, hydnocarpin Substances other than polyphenols Alkaloids Antofine [67,68], avenanthramide, neo-clerodane diterpenoid alkaloids, taspine Terpenes Maslinic acid [69], talaporfin, novel triterpenoids, ent-clerodane diterpenoids, curcuphenol, picrotoxin, solaniol, triptolide, carnosic acid, koetjapic acid, andrographolide, plaunotol, geranylgeraniol Sapogenin Yerba mate tea and mate saponins [70], Paris saponin VII [71] Other substances Polyacetylenes and polyenes [72], chromane derivatives [73], grifolin [74], g-oryzanol [75], yuanhuacine [76], chartreusin [77], simvastatin and lovastatin [78], TPU942 and its derivatives [79], PTZ0025, phytic acid, b-sitosterol, diallyl sulfide, brefeldin A, parthenolide, norcantharidin, protopanaxadiol, melanoidin, evodiamine, 1'-acetoxychavicol acetate, panaxadiol, renieramycin, pyrazolone derivatives, b-asarone, phthalide, turmerone…”
Section: Polyphenolsmentioning
confidence: 99%
“…Crude extract from natural product is considered as having strong cytotoxic activity if the LC 50 value is under 30 mg/ml (Munro et al, 1987;Suffnes & Pezzuto, 1990;Itharat et al, 2004;Chicca et al, 2008). Based on this criterion, the methanolic crude extract of sea cucumber Actinopyga sp.…”
Section: Cytoxicitymentioning
confidence: 99%